Fast Quantum Control of Cavities Using an Improved Protocol without Coherent Errors - Landgraf, Jonas; Flühmann, Christa; Fösel, Thomas; Marquardt, Florian; Schoelkopf, Robert J. (Physical Review Letters, 2024)
The selective number-dependent arbitrary phase gates form a powerful class of quantum gates, imparting arbitrarily chosen phases to the Fock states of a cavity. However, for short pulses, coherent errors limit the performance. Here, we demonstrate in theory and experiment that such errors can be completely suppressed, provided that the pulse times exceed a specific limit. The resulting shorter gate times also reduce incoherent errors. Our approach needs only a small number of frequency components, the resulting pulses can be interpreted easily, and it is compatible with fault-tolerant schemes.
CRIS-Team Scopus Importer:2025-02-04